Effect of sulphur and zinc application on growth and productivity of soybean [Glycine max. (L.) Merrill] in northern plain zone of India - Thenua, O.V.S.; Singh, Kuldeep; Raj, Vivek; Singh, Jasbir (Annals of Agricultural Research, 2014)
A field experiment was conducted during kharif season of 2009 and 2010 at Agronmical Research Farm of Amar Singh College Lakhaoti,Bulandshahr(CCS University, Meerut) with five levels of sulphur (0, 10, 20, 30 and 40 kg S/ha) and four levels of zinc (0, 10, 20 and 30 kg Z/ha) to study the sulphur and zinc requirement of soybean and its effect on yield and their availability status in the soil. The highest yield of soybean was recorded under 40 kg S/ha, it was closely followed by 30 kg S/ha and application of Zinc @ 30 kg/ha recorded higher yield as compared to its lower levels. Available status of sulphur and zinc in soil after harvest of soybean crop was found non-significant.